Prevalence of Zoonotic Sarcocystis spp. Isolated from Cardiac Muscle of Cattle in Muang Chachoengsao District, Chachoengsao Province - ดอกไม้ขาว, อมรรัตน์; สุนทราวิฑูร, พิสิษฐ์; สิงห์ศุข, ชนะพล (KKU Science Journal, 2017)
Sarcocystosis is a zoonotic disease caused by the obligate intracellular protozoan parasites of the genus Sarcocystis. Human infections are acquired by ingesting the raw or undercooked meat containing viable bradyzoites within tissue cysts. The objective of this study was to investigate the prevalence of Sarcocystis spp. in cardiac muscle of cattle collected at fresh markets in Muang Chachoengsao District, Chachoengsao Province, from November, 2015, to March, 2016. The samples were examined by digestion method using pepsin and hydrochloric acid for detecting bradyzoites by light microscope. The overall prevalence of Sarcocystis spp. infection in cardiac muscle of cattle was 43.33% (52/120). The result indicate that consumption of raw or undercooked meat from cattle represents a risk for acquiring intestinal sarcocystosis in Chachoengsao Province.